2009
DOI: 10.1159/000257510
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Signaling Responses of Rat Skeletal Muscle to Brief Endurance Exercise During Hindlimb Unloading: a Catch-Up Process for Atrophied Muscle

Abstract: At times, exercise accompanied by its anabolic effects is not a tractable countermeasure to muscle atrophy. Instead, training is often attempted after the affected muscle has atrophied greatly as a result of unloading. This study was designed to elucidate stress and signaling mechanisms underlying a process of muscle catch-up growth as a result of transitory exercise during unloading. Rats were exercised daily with a routine of 20- or 40-minute treadmill running (at 60% of maximum oxygen uptake) during the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
4
16
1
Order By: Relevance
“…6B), indicating increased FoxO3a activity. This result is consistent with previous reports (25,65). On the other hand, no change in the expression of phosphorylated FoxO3a at Ser 253 was observed during unloading in the suppression of AMPK activity (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…6B), indicating increased FoxO3a activity. This result is consistent with previous reports (25,65). On the other hand, no change in the expression of phosphorylated FoxO3a at Ser 253 was observed during unloading in the suppression of AMPK activity (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…For example, it has been shown that 14-day HS induces a significant reduction in phosphorylated AKT (Ser473) [19,20], p70s6k (Thr389) [19][20][21] and 4E-BP1 [19] in rat soleus muscle. At the same time, some authors did not find an increase in phosphorylated p70s6k (Thr389) in soleus after 10 days of mechanical unloading [22].…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Skeletal muscle cells are susceptible to oxidative stress induced through electron transport and oxygen flux during normal contraction, and this stress may increase with exercise intensity. [1][2][3][4][5][6] Muscle redox status, especially during atrophy, is more oxidative than the redox status in other organs. Augmentation of cellular antioxidant defense presents a basic strategy for controlling oxidative muscle injury and related disease conditions.…”
mentioning
confidence: 99%